2022
DOI: 10.3390/ijms231810665
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Effects of Saponins for the Prevention and Treatment of Cancer by Ameliorating Inflammation and Angiogenesis and Inducing Antioxidant and Apoptotic Effects in Human Cells

Abstract: Saponins are natural compounds found in plants and have a diverse range of applications. However, the therapeutic potential of saponins in regulating cytotoxicity, angiogenesis, and inflammation in mammalian cells is yet to be explored. Here, we investigated the therapeutic effects of saponins from green tea by exploring the cytotoxic effects of saponins by inducing apoptosis in the human cancer cell lines hepatocellular carcinoma (HEPG2) and colorectal adenocarcinoma (HT29). The anti-angiogenesis effect of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Alkaloids are effective in tackling free radicals by performing scavengers against hydroxyl radicals (Gurudeeban et al 2015). Saponins are effective against free radicals by scavenging the radicals, -diphenyl-βpicrylhydrazyl (DPPH), and 2,20 -azino-bis(3ethylbenzothiazoline-6-sulfonic acid (ABTS) and also H2O2 (Khan et al 2022) Triterpenes, -amyrin, oleanolic acid and ursolic acid combat free radicals by scavenging against nitric oxide (NO•), superoxide (•O2-) and lipid peroxides (LOO•) radicals (Santiago et al 2014). These can neutralize free radicals, thereby preventing oxidative damage to most biomolecules and providing significant protection (Sreelatha and Padma 2010).…”
Section: Effect Of Diluent On Spermatozoa Qualitymentioning
confidence: 99%
“…Alkaloids are effective in tackling free radicals by performing scavengers against hydroxyl radicals (Gurudeeban et al 2015). Saponins are effective against free radicals by scavenging the radicals, -diphenyl-βpicrylhydrazyl (DPPH), and 2,20 -azino-bis(3ethylbenzothiazoline-6-sulfonic acid (ABTS) and also H2O2 (Khan et al 2022) Triterpenes, -amyrin, oleanolic acid and ursolic acid combat free radicals by scavenging against nitric oxide (NO•), superoxide (•O2-) and lipid peroxides (LOO•) radicals (Santiago et al 2014). These can neutralize free radicals, thereby preventing oxidative damage to most biomolecules and providing significant protection (Sreelatha and Padma 2010).…”
Section: Effect Of Diluent On Spermatozoa Qualitymentioning
confidence: 99%
“…As for the anticancer, anti-inflammation, and antioxidation effects of saponins, the findings of some researchers can be summarized as follows. Some compounds, such as saponins from plant extracts, exert cytotoxicity effects against cancer cells, such as HTC-8 (human colon carcinoma), BEL-7402 (human liver carcinoma), and A549 (human lung carcinoma) [ 79 ], which may be attributed to the effects of proapoptosis in the cancer cell lines [ 80 ]. Moreover, saponins have been found to inhibit the expressions of the VE-cadherin and VEGFR-2 complexes, which are key growth factors for vascular remodeling and proliferation via NF-κB downregulation [ 80 ].…”
Section: Mechanisms Of Representative Functional Plant Extracts As An...mentioning
confidence: 99%
“…Some compounds, such as saponins from plant extracts, exert cytotoxicity effects against cancer cells, such as HTC-8 (human colon carcinoma), BEL-7402 (human liver carcinoma), and A549 (human lung carcinoma) [ 79 ], which may be attributed to the effects of proapoptosis in the cancer cell lines [ 80 ]. Moreover, saponins have been found to inhibit the expressions of the VE-cadherin and VEGFR-2 complexes, which are key growth factors for vascular remodeling and proliferation via NF-κB downregulation [ 80 ]. Regarding antioxidation effects, saponins exert radical scavenging effects, in turn inhibiting lipid oxidation by breaking chains; therefore, they can function as nutraceuticals and pharmaceuticals [ 80 ].…”
Section: Mechanisms Of Representative Functional Plant Extracts As An...mentioning
confidence: 99%
See 1 more Smart Citation
“…borivilianum usually contains stigmasterol, neotigogenin, hecogenin, alkaloids, phenolic acid, flavonoids, saponins, and palmitic acid ( Visavadiya et al, 2010 ; Giri et al, 2015 ). Among these, stigmasterol ( Pratiwi et al, 2021 ), alkaloids ( Macáková et al, 2019 ), flavonoids ( Jovanovic et al, 1996 ), and saponins ( Khan et al, 2022 ) have been strongly associated with the reduction of oxidative stress and inhibition of ROS generation. Recently, in our previous study, nine compounds have been identified, including 5-methylhex-2-yl pentadecyl ester (23.69%), 9,10-anthracenedione (19.02%), and phthalic acid (18.63%) ( Vyas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%